The non-obvious religiosity of I.A. Bunin's short story "The Caucasus" - A.L. Rodin (Язык и текст)
The article is dedicated to the analysis of the plot and contents of I.A. Bunin's story in a Christian context. The author of the article puts forward a hypothesis about the possible interpretation of the plot of the story as a narrative about sin, its consequences and retribution for sin. The biblical allusions from the Book of Genesis noticed by other researchers – the stay in paradise of the first people – give grounds for an attempt to analyze the entire contents of the story in a biblical context. The article gives an assessment of the mental state of the protagonists and their actions in the spiritual dimension: sin v. virtue. The sins committed by the characters of the story and their inherent passions determine the fatal outcome of the story. Thus, despite the very small proportion of references to the religious context in the text of I.A. Bunin, it is possible to assert the possibility of understanding the story in a Christian way.